Pendidikan Agama Islam Perspektif Al-Ghazali dalam Kitab Ihya’ Ulumuddin - Abdul Kholiq (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2021)
So far, Islamic education is still looking for relevant formulas to form a good system to meet the demands of scientific and technological developments, so that it becomes quality, competitive, and integrative education. Basically the current formulation of education is the result of the manifestation of the thinking of education experts as a solution to the problems of education in its day and is continued as a solution to the problems of education today. Al-Ghazali is a figure thinker and practitioner in the world of Islamic education. The focus of this study is to examine one of his phenomenal works, namely Ihya 'Ulumuddin. The research objective was to analyze the three components of Islamic education in the book, namely the objectives, materials and methods of Islamic religious education. This research is a type of library research with a character and text study approach. Collecting data using document analysis study book Ihya 'Ulumuddin as primary data source, and other relevant references as secondary data sources. Meanwhile, the data analysis technique uses content analysis and interpretation. The findings show that Al-Ghazali's perspective of Islamic religious education aims to achieve the happiness of the Hereafter without neglecting worldly goodness as a means of achieving happiness in the hereafter. The educational method in his thinking refers to two methods of gaining knowledge, namely the method of habituation and thinking under the guidance of a muallim (teacher) and murshid (educator).